Swoistość konstrukcji rozwiązań prawnych a jedność funkcji prawa z perspektywy prawa konstytucyjnego - Syryt, Aleksandra (Kwartalnik Prawa Publicznego, 2017)
The aim of the article is to present whether the specificity of the structure of legal solutions influences the unity of the function of law from the perspective of Polish constitutional law. Preliminary analysis shows that the specificity of constructing legal solutions to constitutional law is related to the functions of law. The nature of legal solutions determines which functions of law will be implemented and to what extent. Regardless of that, the establishment of the law causes the general function of the law to be implemented. The way to implement it may be different, but the shape of legal solutions does not determine that they do not fulfill their role. Despite the specificity of legal solutions in a given branch of law, the unity of the law is preserved. Specific objectives of the law are implemented to a greater or lesser extent depending on the subject matter of the regulation of a given area of law. When analyzing the specificity of the construction of legal solutions to constitutional law, one may wonder whether the generality of these constructs and the lack of regulatory uniformity are desirable from the point of view of the rule of law. The question remains whether there should be tools in the field of constitutional law that will allow the creation of such legal constructs that will better fulfill the functions of the law.